Is Kissing a Bellwether of Sexual and Relationship Satisfaction and Dissatisfaction?. Issue 2 (1st February 2022) - Busby, Dean M.; Hanna-Walker, Veronica; Leavitt, Chelom E.
Abstract: In this study we explored how the amount of kissing during the most recent sexual experience (specific kissing) and amount of kissing during the last year (global kissing) were both associated with the quality of the sexual relationship and overall relationship satisfaction and dissatisfaction. To understand these associations, we obtained surveys from a national sample of 878 participants who had been in a romantic relationship for at least two years. We evaluated their results through a structural equation model and found that for women the rates of specific kissing were associated with their ability to orgasm, sexual frequency, and indirectly to sexual satisfaction. For both men and women, measures of global kissing were associated with both sexual and relationship satisfaction but more strongly with measures of sexual and relationship dissatisfaction. These findings suggest that measures of kissing could be used as a bellwether of both the quality of the sexual relationship for women and of feelings of dissatisfaction about both the sexual and overall relationship for both sexes.